National health insurance, social influence and antenatal care use in Ghana - Nkechi S. Owoo; Monica P. Lambon-Quayefio (Health Economics Review, 2013)
The study explores the importance of social influence and the availability of health insurance on maternal care utilization in Ghana through the use of antenatal care services. A number of studies have found that access to health insurance plays a critical role in women's decision to utilize antenatal care services. However, little is known about the role that social forces play in this decision. This study uses village-level data from the 2008 Ghana Demographic and Health Survey to investigate the effects of health insurance and social influences on the intensity of antenatal care utilization by Ghanaian women. Using GIS information at the village level, we employ a spatial lag regression model in this study. Results indicate that, controlling for a host of socioeconomic and geographical factors, women who have health insurance appear to use more antenatal services than women who do not. In addition, the intensity of antenatal visits appears to be spatially correlated among the survey villages, implying that there may be some social influences that affect a woman's decision to utilize antenatal care. A reason for this may be that women who benefit from antenatal care through positive pregnancy outcomes may pass this information along to their peers who also increase their use of these services in response. Traditional/Cultural leaders as 'gate-keepers' may be useful in the dissemination of maternal health care information. Public health officials may also explore the possibility of disseminating information relating to maternal care services via the mass media.
Keywords: 330; antenatal care; health insurance; social influence; child and maternal health; maternal mortality; spatial analysis; Sterblichkeit; Krankenversicherung; Soziale Beziehungen; Basisgesundheitsversorgung; Ghana